2006
DOI: 10.1111/j.1747-6593.2005.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of aeration performance in stepped spillways

Abstract: Dissolved oxygen content is a prime indicator of water quality. The oxygen transfer across the air-water interface at a hydraulic structure, such as a weir or spillway, occurs by self-aeration along the chute and by flow aeration in the hydraulic jump at the downstream end of the structure. Despite increased research activities in the field of stepped spillways, the aeration efficiency of stepped spillways is not yet known. This paper investigates the aeration efficiency of stepped spillways, in particular the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 31 publications
4
15
0
4
Order By: Relevance
“…The results in Figures 7a-7c, for the aeration efficiency as a function of the ratio of the length of aeration to the stepped roughness height, indicated that E20 increases as La/Ls increases. [14] stated that length of aeration increases with an increase in overall aeration efficiency; this also agrees with the statement of [20] that aeration efficiency decreases with an increase in the ratio of non-aerated length to stepped height. Aeration efficiency in Figures 8a-8c showed that it decreases as roughness Froude number Fe increases.…”
Section: Determination Ofsupporting
confidence: 78%
See 2 more Smart Citations
“…The results in Figures 7a-7c, for the aeration efficiency as a function of the ratio of the length of aeration to the stepped roughness height, indicated that E20 increases as La/Ls increases. [14] stated that length of aeration increases with an increase in overall aeration efficiency; this also agrees with the statement of [20] that aeration efficiency decreases with an increase in the ratio of non-aerated length to stepped height. Aeration efficiency in Figures 8a-8c showed that it decreases as roughness Froude number Fe increases.…”
Section: Determination Ofsupporting
confidence: 78%
“…Aeration efficiency in Figures 8a-8c showed that it decreases as roughness Froude number Fe increases. Froude number is a function of the velocity; it is when the velocity is dissipated that aeration is enhanced; this agrees with the statement of [20] that aeration efficiency decreases with an increase in roughness Froude number. (11) was validated, taking the unit discharge of 26.1 L/s.m and value of aeration efficiency for two models from each chute geometry as an example, there is good agreement between them, as shown on Table 7.…”
Section: Determination Ofsupporting
confidence: 72%
See 1 more Smart Citation
“…Elle est souvent calculée à une température de référence de 20 °C en utilisant l'équation de GULLIVER et al (1990) : La majorité des études existantes (BAYLAR et al, 2006(BAYLAR et al, , 2007TOOMBES et CHANSON, 2005) n'intègrent pas la totalité des paramètres significatifs. De plus, les débits d'eau étudiés sont assez élevés et ne correspondent pas aux débits dans les petites rivières.…”
Section: Transfert D'oxygène Air-eauunclassified
“…Plus tard, TOOMBES et CHANSON (2005) ont étudié l'oxygénation sur un canal d'eau avec des marches d'escaliers à des dimensions proches de celles à l'échelle réelle. BAYLAR et al (2003BAYLAR et al ( , 2006BAYLAR et al ( , 2007 ont caractérisé l'oxygénation par des corrélations empiriques grâce à des mesures sur un pilote de laboratoire. Il existe d'autres approches qui ont été utilisées pour caractériser l'aération par les cascades.…”
Section: Introductionunclassified